Provincial-Municipal Grants and Intercountry Equity: An Empirical Study of County Income Redistribution through Ontario Grant Programmes - Ronald W. Crowley (Queen's University, Department of Economics, 1969)
The purpose of this study is twofold: (1) to examine which municipal governments are net beneficiaries of the Ontario programme of intergovernmental transfers and (2) to determine whether distribution of grants equitably reflects differences amongst municipal units.
Keywords: 330